Double Victimization in the Workplace: Why Observers Condemn Passive Victims of Sexual Harassment - Diekmann, Kristina A.; Walker, Sheli D. Sillito; Galinsky, Adam D.; Tenbrunsel, Ann E. (Organization Science, 2013)
Five studies explore observers' condemnation of passive victims. Studies 1 and 2 examine the role of observers' behavioral forecasts in condemning passive victims of sexual harassment. Observers generally predicted that they would engage in greater confrontation than victims typically do. More importantly, the more confrontation participants predicted they would engage in, the more they condemned the passive victim, and the less willing they were to recommend the victim for a job and to work with her. Study 3 identifies the failure to consider important motivations likely experienced by victims—and that contribute to their passivity—as an important driver of behavioral forecasting errors. Having forecasters reflect on motivations normally experienced but not typically forecast produced behavioral predictions that were more consistent with the actual passive behavior of sexual harassment victims. Studies 4 and 5 reduce condemnation of passive sexual harassment victims by highlighting important motivations likely experienced by those victims (Study 4) and by having participants recall a past experience of not acting when being intimidated in the workplace, a situation related but distinct from sexual harassment (Study 5). The results from these studies add insights into the causes and consequences of victim condemnation and help explain why passivity in the face of harassment—the predominant response—is subject to so much scorn.